Health and lifestyle of Nepalese migrants in the UK - van Teijlingen Edwin R; Simkhada Padam P; Adhikary Pratik; Raja Amalraj E (BMC, 2008)
Abstract Background The health status and lifestyle of migrants is often poorer than that of the general population of their host countries. The Nepalese represent a relatively small, but growing, immigrant community in the UK, about whom very little is known in term of public health. Therefore, our study examined the health and lifestyle of Nepalese migrants in the UK. Methods A cross-sectional survey of Nepalese migrants in UK was conducted in early 2007 using a postal, self-administered questionnaire in England and Scotland (n = 312), and telephone interviews in Wales (n = 15). The total response rate was 68% (327 out of 480). Data were analyzed to establish whether there are associations between socio-economic and lifestyle factors. A multivariate binary logistic regression was applied to find out independent effect of personal factors on health status. Results The majority of respondents was male (75%), aged between 30 and 45 (66%), married or had a civil partner (83%), had university education (47%) and an annual family income (69%) ranging from £5,035 to £33,300. More than one third (39%) of the respondents have lived in the UK for 1 to 5 years and approximately half (46%) were longer-term residents. Most (95%) were registered with a family doctor, but only 38% with a dentist. A low proportion (14%) of respondents smoked but more than half (61%) consumed alcohol. More than half (57%) did not do regular exercises and nearly one fourth (23%) of respondents rated their health as poor. Self reported 'good' health status of the respondents was independently associated with immigration status and doing regular exercise Conclusion The self reported health status and lifestyle, health seeking behaviour of Nepalese people who are residing in UK appears to be good. However, the overall regular exercise and dentist registration was rather poor. Health promotion, especially aimed at Nepalese migrants could help encourage them to exercise regularly and assist them to register with a dentist.